PERGELARAN VICOLMING WAYANG BEBER 4 KOTA SEBAGAI SOLUSI DAMPAK COVID-19 - Sugihartono, Ranang Agung; Rianto, Jaka; Marwati, Sri (Institut Seni Indoensia Surakarta, 2021)
The Covid-19 pandemic changed all the aspects of life, including the arts. Traditional artists were badly affected. They do not have any requests for art performances at all, because the performances will definitely gather the masses, including the beber puppet (wayang beber). For that, it is necessary to find a solution to overcome this condition. Through this artistic research, the researcher created a model for presenting the beber wayang show using multi-platform technology, namely the integration of video conferencing and live streaming, abbreviated as Vicolming. This artistic research uses a type of practice-based research with a ‘Multi-Method’ approach with stages including information gathering, selection, preparation, analysis, evaluation, presentation, and communication. The results show that the wayang beber show performed with multi-platform technology can produce offerings or performance that are not only online but interesting, creative, interactive, collaborative, and can be watched from anywhere live and on demand. The results of this research are expected to become an online performance model that can be applied to other traditional performing arts.Keywords: Vicolming, multi-platform, wayang beber, and Covid-19